2017
DOI: 10.1038/ncomms14347
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing actin patterns shape membrane architecture but not cell mechanics

Abstract: Cell-free studies have demonstrated how collective action of actin-associated proteins can organize actin filaments into dynamic patterns, such as vortices, asters and stars. Using complementary microscopic techniques, we here show evidence of such self-organization of the actin cortex in living HeLa cells. During cell adhesion, an active multistage process naturally leads to pattern transitions from actin vortices over stars into asters. This process is primarily driven by Arp2/3 complex nucleation, but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(146 citation statements)
references
References 61 publications
16
130
0
Order By: Relevance
“…Whether the arcs themselves are involved in stabilizing the synapse and how they may communicate with the foci-actomyosin system to co-ordinate synapse stability remains to be investigated. Similarly, another study recently reported actin "vortice -like foci" that are interconnected by the actomyosin network in NK cells (Carisey et al, 2018;Fritzsche et al, 2017). It remains unclear whether the NK cell "vortices-like foci" cytoskeleton reported previously and the foci described here have related functions or involve similar molecular mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…Whether the arcs themselves are involved in stabilizing the synapse and how they may communicate with the foci-actomyosin system to co-ordinate synapse stability remains to be investigated. Similarly, another study recently reported actin "vortice -like foci" that are interconnected by the actomyosin network in NK cells (Carisey et al, 2018;Fritzsche et al, 2017). It remains unclear whether the NK cell "vortices-like foci" cytoskeleton reported previously and the foci described here have related functions or involve similar molecular mechanisms.…”
Section: Discussionsupporting
confidence: 56%
“…temperature and/or lipid composition) not normally conducive for phase transitions. A proof-of-principle for this mechanism has been recently demonstrated in vitro 159 , by showing that dynamically remodelling actomyosin networks can organize an associated synthetic membrane, while these self-organising cortical actin patterns have been shown to associate more ordered membrane environments in the plasma membrane of living cells 160 . Adding to the chemical principles of lipid–lipid interactions, this actin-driven mechanism of membrane ordering allows to explain the dynamic properties and non-equilibrium distribution of actin–dependent nanoclusters formed by several lipid species, which have been observed in.…”
Section: Mechanisms Of Domain Regulationmentioning
confidence: 97%
“…For example, cortical actin assemblies (asters), known to bind and therefore immobilize PS in the inner leaflet, have also been purported to induce clustering of glycophosphatidylinositol (GPI)-anchored proteins on the outer leaflet with important consequences to cell signaling [30]. Proteins tethered by lipid associations, such as GPI, palmitoyl, myristoyl, or cholesterol, are already preferentially segregated to higher ordered lipid raft domains [31].…”
Section: Plasma Membrane Proteins Contribute To the Formation Of Lipimentioning
confidence: 99%